THE EFFECTS OF MATERIALS AND SHAPE OF THE SHIELDING DISK ON PERCENTAGE DEPTH DOSE (PDD) ON INTRA-OPERATIVE RADIATION THERAPY (IORT) - Amalia, Annisa
Treatment of breast cancer in early-stage can use Intra-operative Radiation Therapy (IORT) technique as an alternative to the conventional techniques, External Beam Radiotherapy (EBRT). IORT is equipped with an applicator and shielding disk that can maximize the radiation. The shielding disk serves to minimize radiation received by normal tissue and is also used to optimize irradiation of the target with backscattering radiation generated from the material used. In this study, will be studied the effects of materials and shape of the shielding disk on the Percentage Depth Dose (PDD) in the case of early-stage breast cancer. The shielding disk has a 5 cm diameter and 0.8 cm thick that consisting two different material. The materials that will be varied are Polymethylmethacrylate (PMMA), Aluminum (Al), Gold (Au) and Lead (Pb). And it will also vary the two types of shielding disk, FLAT type and STEP type, to determine which combination of materials gives maximum results and which design of shielding disk are the most optimal. The results showed that Gold (AU) can be an alternative material that can uses to be a shielding disk because the gold can absorb energy maximumly. And the shape of shielding disk STEP’s type with the combination of material is Pb-Au can provide more optimal radiation to the target because it can be more maximal to kill the remaining cancer in tumor bed.